PENGARUH GREEN ACCOUNTING, CORPORATE SOCIAL RESPONSIBILITY (CSR), UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI - Berliana Nova, Chairunisa; Yamin, Mohamad (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2025)
This study aims to analyze the effects of Green Accounting, Corporate Social Responsibility (CSR), and Firm Size on Financial Performance as measured by Return on Assets (ROA) among banking companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. A quantitative approach was employed using secondary data from annual reports and sustainability reports. The sample consisted of 12 banking companies, yielding 48 observations over the four-year span.The data analysis included descriptive statistics, classical assumption testing, and multiple linear regression using SPSS 26. The results reveal that, individually, Green Accounting and Firm Size have a positive and significant impact on ROA, while CSR has a negative but significant effect. Collectively, the three independent variables significantly influence financial performance. The coefficient of determination (R²) is 39.8%, indicating that Green Accounting, CSR, and Firm Size explain 39.8% of the variance in financial performance, with the remainder influenced by factors outside the model.